Generic definition, key, and two new species of Polyphrix Townes (Hymenoptera: Ichneumonidae: Cryptinae) from the Atlantic Forest - Nogueira, Liana K.; Aguiar, Alexandre P. (Zootaxa, 2005)
Two new species, Polyphrix atlantica sp. n. and P. cristata sp. n., are described from southeastern Brazil, representing the first records of the genus in the Atlantic Forest. Only one species was previously known, P. varians Townes, from northern Brazil; its occurrence in Peru is refuted. The definition of the genus Polyphrix Townes is revised and expanded. Illustrations and a key to species are provided.